Cytological Analysis of Oral Mucosal Changes in Smokers: Insights from AgNOR Counts and Papanicolaou Staining - Elmahdi, Faris M.; Salim, Lina A.; Kabeer, Sumia S.; Kareembakhsh, Jori O.; Alshinqiti, Amina J.; Atom, Sarah M; Shaaeldin, Abdelrahim (Achievements and Challenges of Medicine and Medical Science Vol. 4, 2024)
Objective: The goal of this chapter is to look at the cytological changes that happen in smokers' mouth linings, specifically the cell changes and proliferation seen using Argyrophilic Nucleolar Organizer Region (AgNOR) counts along with Papanicolaou (Pap) staining. Methodology: Oral mucosal smears from 500 individuals, aged between 18 and 80 years, were collected in Al Madinah Al Munawara. The AgNOR counting and Pap staining were employed to evaluate cytological alterations such as atypia, inflammation, dysplasia, keratinization, and the proliferative activity of epithelial cells. Results: Smokers exhibited significantly higher AgNOR counts per nucleus compared to nonsmokers (1.99 ± 3.53 vs. 0.42 ± 1.22). 42.3% of smokers and 20% of nonsmokers showed inflammatory changes. Multinucleated cells and cytological atypia in 11% of smokers, but not in the control group, were detected. These findings suggest increased proliferative activity among smokers, even in the absence of visible clinical lesions. Conclusion: Pap staining alone does not provide sufficient information to detect smoking-related changes in the oral mucosa. Using both Pap staining and the AgNOR technique together makes it easier to find cytological abnormalities and proliferative activity. This gives a more complete picture of how smoking affects the oral mucosa.